Ontogeny of critical swimming speed of wild-caught and laboratory-reared red drum Sciaenops ocellatus larvae - Faria, Ana M. (2018)
Critical swimming speed (U,,it) provides a useful estimate of maximum swimming performance for fish larvae that can be used to assess transport and migratory potential. We measured U,it of red drum Sciaenops ocellatus larvae through its ontogeny and compared the swimming performance of laboratory-reared larvae to that of wild-caught individuals. U-crit increased with ontogeny (size), even though variability in U-crit at any ontogenetic state was large. U-crit for wild-caught larvae increased from 9.7 to 22.2 cm s(-1) over the range of 8.3 to 16.3 mm TL and from 1.1 to 20.5 cm s(-1) over the range of 3.0 to 19.1 mm TL for reared larvae. The ontogenetic increase in critical swimming speed occurred in 2 phases-an early phase of rapid improvement, and a later phase of slower improvement. This sharp change in the trajectory of swimming performance coincided with important changes in ecology, morphology, and hydrodynamics. During the early phase, larvae were pelagic, their growth was highly allometric, especially in the caudal region, and they swam in the inertial hydrodynamic regime. The onset of the later phase coincided with settlement into seagrass beds, isometric growth, and inertial effects on locomotion. Wild larvae generally exhibited greater values of U,it than reared larvae of a comparable size, but the difference was not statistically significant. The results of this comparison imply that research on reared larvae may provide naturalistic results for swimming performance and that hatchery-produced larvae may perform certain behaviours well when released into the wild.